Mitos Kecantikan Perempuan dalam Karya Seni Tiga Dimensi - Prasetya, Laras Shinta; P.A, Albertus Rusputranto (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2023)
The creation of this Tugas Akhir Course (Final Project) departs from the writer's anxiety about people's response to women who are considered not beautiful. This is one of the impacts of beauty myths that are felt by women. On this Final Assignment the writer creates three dimensional works of art with a source of inspiration the myth of female beauty. On the creation of these three dimensional works of art, an experiment was carried out with stick glue medium. This Final Assignment departs from the visual concept and method of creation by Joris Kuipers. Kuipers creates installation art in the figurative abstractionism style. Joris Kuipers' method of creation and figurative abstractionism style the basis for the realization of these three dimensional works of art. The creation method used by Kuipers has three stages; the idea exploration stage, the initial idea development stage, and the media experiment stage. The creation of Final Assignment aims to criticize the myth of female beauty.